Penerapan Antropometri Terhadap Perancangan Alat Stunting Pengukur Tinggi dan Berat Badan Anak-anak yang Ringkas dan Sistematis - Rifki, Ahmad Muhson; Santoso, Heru Agus (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Routine health checks, especially anthropometric measurements such as height and weight, are very important for the prevention and early detection of stunting in early childhood (1-5 years). Stunting caused by long-term malnutrition can inhibit physical growth and brain development in children, thus affecting their productivity in the future. However, manual measurements that are still widely used have various obstacles, such as low accuracy, potential bias, and long implementation time. Conventional measuring instruments are often not optimal due to limitations in accuracy, safety, and comfort, especially in Posyandu. Therefore, it is necessary to design a height and weight measuring instrument that is integrated, ergonomic, lightweight, safe, and attractive for children, to make it easier for Posyandu cadres and health workers to detect stunting more accurately and efficiently.